Effectiveness of Induced Polarisation Method in Identifying the Presence of Minerals: 2-Dimensional Interpretation Modeling of Crossing Lines - Fajri Farid; Vico Luthfi Ipmawan; Rizqi Prastowo (CV FOUNDAE, 2024)
This study evaluates the effectiveness of the Induced Polarization (IP) method in identifying mineral presence within the Pacitan region through a detailed case study utilizing 2-dimensional (2D) interpretation of crossing lines. The Pacitan region, with its diverse geological structures, offers an ideal test site for assessing the IP method's capabilities in mineral exploration. By conducting extensive IP surveys and integrating the data with geological and geophysical information, distinct anomalies indicative of mineralization were identified. The results demonstrate that the IP method is highly effective in detecting subsurface minerals, providing a reliable tool for exploration. The 2D interpretation of crossing lines significantly improved the accuracy of anomaly detection and offered detailed insights into the spatial distribution of mineral deposits. Based on the IP survey results, a large resistivity anomaly is located at a distance of 40 metres from the starting point of measurement with a depth of 2-20 metres and a diameter of about 40 metres. Meanwhile, the chargeability anomaly is at a distance of 30 metres from the starting point with a depth of 4-24 metres and a diameter of about 30 metres. When observed from each analysis of line 1 and 2, the cross results can identify resistivity and chargeability anomalies very accurately. This research highlights the potential of the IP method as a non-invasive, cost-effective approach for mineral exploration, particularly in geologically complex regions like Pacitan. The findings underscore the method's utility in enhancing mineral prospecting efforts and contributing to more efficient exploration strategies.